Heart-lung crosstalk in acute respiratory distress syndrome - Rocha, Nazareth N.; Silva, Pedro L.; Battaglini, Denise; Rocco, Patricia R. M. (Frontiers in Physiology, 2024)
Acute Respiratory Distress Syndrome (ARDS) is initiated by a primary insult that triggers a cascade of pathological events, including damage to lung epithelial and endothelial cells, extracellular matrix disruption, activation of immune cells, and the release of pro-inflammatory mediators. These events lead to increased alveolar-capillary barrier permeability, resulting in interstitial/alveolar edema, collapse, and subsequent hypoxia and hypercapnia. ARDS not only affects the lungs but also significantly impacts the cardiovascular system. We conducted a comprehensive literature review on heart-lung crosstalk in ARDS, focusing on the pathophysiology, effects of mechanical ventilation, hypoxemia, and hypercapnia on cardiac function, as well as ARDS secondary to cardiac arrest and cardiac surgery. Mechanical ventilation, essential for ARDS management, can increase intrathoracic pressure, decrease venous return and right ventricle preload. Moreover, acidemia and elevations in transpulmonary pressures with mechanical ventilation both increase pulmonary vascular resistance and right ventricle afterload. Cardiac dysfunction can exacerbate pulmonary edema and impair gas exchange, creating a vicious cycle, which hinders both heart and lung therapy. In conclusion, understanding the heart-lung crosstalk in ARDS is important to optimize therapeutic strategies. Future research should focus on elucidating the precise mechanisms underlying this interplay and developing targeted interventions that address both organs simultaneously.